The effect of use of social robot nao on children's motivation and emotional states in special education - Namlısesli, Deniz; Baş, Hale Nur; Bostancı, Hilal; Coşkun, Buket; Erol Barkana, Duygun; Tarakçı, Devrim (My University, 2024)
The utilization of social robots in therapeutic and educational settings offers promising advancements, especially for children with special needs. 21 children receiving special education at Dilbade Special Education and Rehabilitation Center were evaluated under two conditions: sessions led by special education teachers and those supported by the social robot NAO. The Pediatric Motivation Scale (PMS) results demonstrate that special education sessions involving the social robot NAO increased the children's motivation compared to traditional sessions. Moreover, statistical features from the physiological signals, including Blood Volume Pulse (BVP), Electrodermal Activity (EDA), and Skin Temperature (ST) were found. Notably, all significant features from BVP, EDA, and ST have increased, which indicated that children were excited and felt positive during the sessions involving the social robot NAO. Furthermore, the subjective evaluations from children, families, and special education teachers supported the quantitative findings, with a majority expressing enthusiasm for including the social robot NAO in special education.
Keywords: NAO; Physiological Signals; Social Robot; Special Education